2020
DOI: 10.1155/2020/2093593
|View full text |Cite
|
Sign up to set email alerts
|

A New Equilibrium Strategy of Supply and Demand for the Supply Chain of Pig Cycle

Abstract: The pig market had experienced a cycle of price rise and fall, also known as the “pig cycle.” This paper analyzes the fluctuation relationship between pig price, pig supply, and pork demand, constructs a system dynamics model of the pig industry by decomposing the structure of the pig supply chain, and then discusses the causes of “pig cycle,” as well as the supply chain management strategy and industrial policy, to stabilize the pig industry market. Research shows that reducing the cost of pig breeding, count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…Therefore, the Chinese government should reduce excessive intervention in pork prices and let the market play a role in the pig and pork market [1]. By decomposing the structure of the pig supply chain, Lu et al [2] constructed a dynamic model of the pig industry system and found that reducing pig breeding cost is the most effective long-term strategy to stabilize pig price. Ngarava and Mushunje [3] found that Zimbabwe's pork industry participants' pricing strategy was short-sighted when they studied the pricing strategy in the dynamic institutional environment of land reform and innovation policy in Zimbabwe.…”
Section: Research On the Control Policy Of Pig Pricementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the Chinese government should reduce excessive intervention in pork prices and let the market play a role in the pig and pork market [1]. By decomposing the structure of the pig supply chain, Lu et al [2] constructed a dynamic model of the pig industry system and found that reducing pig breeding cost is the most effective long-term strategy to stabilize pig price. Ngarava and Mushunje [3] found that Zimbabwe's pork industry participants' pricing strategy was short-sighted when they studied the pricing strategy in the dynamic institutional environment of land reform and innovation policy in Zimbabwe.…”
Section: Research On the Control Policy Of Pig Pricementioning
confidence: 99%
“…By word segmentation of all policy texts, the author then uses Python software to generate 5 categories of subject words. Equation ( 1) is the expression of Dirichlet distribution; thus, the conditional distribution of documents is calculated, as shown in Equation (2). Then, Equation ( 3) is used to obtain the joint distribution of the subject words.…”
Section: Establishment Of Pmc Index Systemmentioning
confidence: 99%
“…Customer satisfaction with the front warehouses is determined by factors such as distribution time, pickup distance, service price, service quality, and goods turnover ability [7]. As https://www.pupumall.com delivers goods directly to the door without the need for customers to pick up the goods themselves, customer satisfaction mainly depends on the distribution time, since the logistics distribution market is quite transparent and the prices are consistent, so they do not need to be considered.…”
Section: Problem Prototypes and Modelsmentioning
confidence: 99%
“…Formula (3) represents the function of customer satisfaction, which is determined by three factors, namely, the distribution time (s 1i ), goods turnover capacity (s 2 ), and service quality (s 3i ), which can be obtained by formulas ( 4)- (6). In formula (4), st ij represents the membership degree of terminal customers j to a front warehouse i in terms of distribution time, which can be calculated using formula (7). Similarly, the customer satisfaction of customer on turnover capacity involved in formula ( 5) can be calculated by formula (8), in which α and β in the function represent the customized coefficients for customers.…”
Section: Solution Modelmentioning
confidence: 99%
See 1 more Smart Citation